Evaluation technology and practice of continental shale oil development in China - Yang LI; Qingmin ZHAO; Qi LYU; Zhaojie XUE; Xiaopeng CAO; Zupeng LIU (Petroleum Exploration and Development, 2022)
This paper analyzes the differences in geological and development characteristics between continental shale oil in China and marine shale oil in North America, reviews the evaluation methods and technological progress of the continental shale oil development in China, and points out the existing problems and development directions of the continental shale oil development. The research progress of development evaluation technologies such as favorable lithofacies identification, reservoir characterization, mobility evaluation, fracability evaluation, productivity evaluation and geological-mathematical modeling integration are introduced. The efficient exploration and development of continental shale oil in China are faced with many problems, such as weak basic theoretical research, imperfect exploration and development technology system, big gap in engineering technology between China and other countries, and high development cost. Three key research issues must be studied in the future: (1) forming differentiated development technologies of continental shale oil through geological and engineering integrated research; (2) strengthening the application of big data and artificial intelligence to improve the accuracy of development evaluation; (3) tackling enhanced shale oil recovery technology and research effective development method, so as to improve the development effect and benefit.